Intraoperative Neuromonitoring During Resection of Gliomas Involving Eloquent Areas - You, Hao; Qiao, Hui (Frontiers in Neurology, 2021)
In the case of resection of gliomas involving eloquent areas, equal consideration should be given to maintain maximal extent of resection (EOR) and neurological protection, for which the intraoperative neuromonitoring (IONM) proves an effective and admirable approach. IONM techniques applied in clinical practice currently consist of somatosensory evoked potential (SSEP), direct electrical stimulation (DES), motor evoked potentials (MEP), electromyography (EMG), and Electrocorticography (ECoG). The combining use of DES and ECoG has been adopted widely. With the development of technology, more effective IONM tactics and programs would be proposed. The ultimate goal would be strengthening the localization of eloquent areas and epilepsy foci, reducing the incidence of postoperative dysfunction and epilepsy improving the life quality of patients.